2017
DOI: 10.1209/0295-5075/118/60007
|View full text |Cite
|
Sign up to set email alerts
|

From quantum coherence to quantum correlations

Abstract: In quantum mechanics, quantum coherence of a state relative to a quantum measurement can be identified with the quantumness that has to be destroyed by the measurement. In particular, quantum coherence of a bipartite state relative to a local quantum measurement encodes quantum correlations in the state. If one takes minimization with respect to the local measurements, then one is led to quantifiers which capture quantum correlations from the perspective of coherence. In this vein, quantum discord, which quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 52 publications
0
32
0
1
Order By: Relevance
“…The anonymity resources should arguably be viewed as a hybrid of coherence and correlation. One could describe it as correlated coherence, though this appears distinct from the correlated coherence of [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anonymity resources should arguably be viewed as a hybrid of coherence and correlation. One could describe it as correlated coherence, though this appears distinct from the correlated coherence of [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…We can view WA states as having correlated coherence in the eigenbasis of the unitaries. There is a formal similarity with the correlated coherence defined in [34][35][36][37].…”
Section: Form Of Useful States 31 Form Of Wa Statesmentioning
confidence: 99%
“…Recently, the coherence measures are generalized to Lüders measurement picture as a partial coherence quantification [21] [22] [23] [24]. In this section we show that the coherence measure in terms of quantum Tsallis relative entropy can be also generalized into this setting.…”
Section: Quantum Coherence Measure In Lüders Measurement Picturementioning
confidence: 99%
“…[26][27][28][29][30][31][32][33][34][35][36][37][38][39] The same is true for its counterpart quantity, [40][41][42] that is, the measurementinduced nonlocality (MIN) which characterizes the global disturbance in a composite state caused by a local nondisturbing measurement on one subsystem. In particular, with the development of the resource theory of quantum coherence, [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] it was shown that the coherence of a system could be converted through incoherent operations into the SQD, instead of the asymmetric QD, of a composite system. [42][43][44][45][46][47][48][49] However, neither the QD nor the MIN of a bipartite system is symmetric in the sense that different results will be obtained (especially for some zero-discord states) if the two subsystems are swapped, which implies that the QD and MIN cannot completely quantify all of the quantum correlations present in a state.…”
Section: Introductionmentioning
confidence: 99%
“…[40] Recently, some progress has been made in regard to analytical expressions for certain classes of states or effective numerical methods. [54,65,66] By considering different bases, the coherence can also be related to the SMIN. To overcome this shortcoming, symmetric versions of the QD and the MIN are defined, that is, the symmetric quantum discord (SQD) [50][51][52] and the symmetric measurement-induced nonlocality (SMIN).…”
Section: Introductionmentioning
confidence: 99%